Artículos Los lugares espacian el espacio1 - Aldo Hidalgo Hermosilla (2018)
In August 1951, in the city of Darmstadt, philosopher Martin Heidegger gave the lecture "Building Dwelling Thinking". From that reflection, architectural theory has been nurtured with substantial arguments that allowed rethinking space; not as a geometric matrix for the physical-technical project, centerpiece of modernist aesthetics, but as something built and lived; this is, as a place. In this essay, following the guidelines of Heidegger, we outline the idea that if the famous text is examined together with the hut that the philosopher occupied in the town of Todtnauberg, in Germany, we may glimpse a notion linked to the existence: the one of space-place. And, this notion, in turn, leads us to the question of space as such.